What Have We Learnt About the Mechanisms of Rapid Water Transport, Ion Rejection and Selectivity in Nanopores from Molecular Simulation?. Issue 8 (25th January 2014) - Thomas, Michael; Corry, Ben; Hilder, Tamsyn A.
<x xml:space="preserve">Abstract</x> Nanopores have demonstrated an extraordinary ability to allow water molecules to pass through their interiors at rates far exceeding expectations based on continuum theory. Moreover, simulation studies suggest that particular nanoscale pores have the potential to discriminate between water and salts as well as to distinguish between a range of different ion types. Some of the unusual features of transport in these nanopores have been elucidated with molecular dynamics simulation, specifically the spontaneous filling and rapid transport of water, the rejection of ions and the selection between ions. The main focus of this review, however, is the physical mechanisms which act to produce such remarkable behaviour at this scale, drawing on the many studies that have been conducted in the last decade. Since molecular dynamics simulations allow the motion of individual atoms to be followed over time, they have the potential to provide fundamental insight into the reasons why transport in nanoscale pores differs from expectations based on macroscopic theory. Gaining an understanding of the mechanisms of transport in these tiny pores should guide future experiments in this area aimed at developing novel technologies and improving existing membrane separation techniques.